Preparation Methods for Improving PEEK’s Bioactivity for Orthopedic and Dental Application: A Review - Almasi, Davood; Iqbal, Nida; Sadeghi, Maliheh; Sudin, Izman; Abdul Kadir, Mohammed Rafiq; Kamarul, Tunku (International Journal of Biomaterials, 2016)
There is an increased interest in the use of polyether ether ketone (PEEK) for orthopedic and dental implant applications due to its elastic modulus close to that of bone, biocompatibility, and its radiolucent properties. However, PEEK is still categorized as bioinert due to its low integration with surrounding tissues. Many studies have reported on methods to increase the bioactivity of PEEK, but there is still one-preparation method for preparing bioactive PEEK implant where the produced implant with desirable mechanical and bioactivity properties is required. The aim of this review is to present the progress of the preparation methods for improvement of the bioactivity of PEEK and to discuss the strengths and weaknesses of the existing methods.